Measurement Of Occupational Safety And Health Risk Levels Of Kadiri University LP3M Building - Sony Susanto; Hendy Hendy; Budi Winarno; Agata Iwan Candra (U Karst, 2020)
Construction work for high rise buildings is a dense work activity with a high level of risk. The purpose of this research is that construction of the building takes place in the middle of lecture activities where many students, lecturers, and staff carry out activities in the campus environment, considering that construction projects are generally vulnerable to work accidents. This study investigated the identification, K3 risk assessment, and how to control OHS risks in Kadiri University LP3M building projects. The assessment method uses a matrix sourced from AS / NZS 4360: 2004. The study population numbered 58 workers ranging from workers, artisans, project guards, forepersons, executors, and office staff. The sample in this study amounted to 38 respondents. Data collected from questionnaires to respondents. The results of the study showed that immovable/ tripped objects with a risk index of 20 included a very high-risk classification, high-risk classification of 4 variables, classification at medium risk level as many as ten variables can endanger workers and jobs while classification at a low-risk level as much as two variables.